Fluctuating fish asymmetry in natural and artificial reservoirs of Dnipro region on example of invasion types - Horchanok, Anna; Horchanok, A.; Horchanok, A. V.; Горчанок, Анна Володимирівна (Дніпровський ДАЕУ, 2019)
Researches of fluctuating asymmetry of the bilateral features of fish were conducted in 2018 on the natural reservoirs (the Samara River within Novomoskovsk and Pavlograd districts of Dnipropetrovsk region, the reservoirs of the Dnipro-Oril Nature Reserve). Insignificant deviations from the bilateral symmetry of external features in living organisms may indicate a decrease in the vitality of certain populations. Using of mass, widespread fish species as the test objects is the best way to detect the levels of fluctuating asymmetry. The fluctuating asymmetry of four bilateral features was estimated within 146 units of the common sunfish Lepomis gibbosus, the stone moroco of Pseudorasbora parva and the round goby Neogobius melanostomus in different habitat conditions, the stability of their life circle was evaluated. The number of rays in the interbranchial septum, the number of branching rays in the pectoral and abdominal fins, the number of scales in the lateral line were analysed. The variability of these features on the left and right sides of the fish was evaluated. The lowering of the natural fish populations vitality because of the influence of negative anthropogenic pressure is currently minor. The stability of fish development by the analysis of bilateral features is noted within normal limits of 1 point (Neogobius melanostomus from the reservoirs of the Dnipro-Oril Nature Reserve, Lepomis gibbosus and Pseudorasbora parva from the middle section of the Samara River) or deviates insignificantly from the statutory indicator in 2 points (Lepomis gibbosus from the lower section of the Samara River). Species of Neogobius melanostomus from the reservoirs of the Dnipro-Oril Nature Reserve show the lowest quantitative indices of the bilateral features asymmetry (0.17 of asymmetric detections per feature). This may demonstrate the absence of negative anthropogenic impact on ground fish within the particularly guarded water areas. The application of the analysis of the fluctuating fish asymmetry is the simplest and most accessible way of rapid testing of the water environment state, but complex laboratory studies, including molecular and biochemical ones, must be used to obtain a more accurate and reliable estimate. Дослідження флуктуючої асиметрії білатеральних ознак риб проводили у 2018 р. на природних водоймах (ріки Самара у межах Новомосковського та Павлоградського районів Дніпропетровської області, водойми природного заповідника «Дніпровсько-Орільський»). Незначні відхилення від білатеральної симетрії зовнішніх ознак у живих організмів можуть вказувати на зниження життєздатності певних популяцій. Використання масових, широко розповсюджених видів риб, як тест-об’єктів – оптимальний способ виявлення ступеня флуктуючої асиметрії. Досліджували флуктуючу асиметрію чотирьох білатеральних ознак у сонячного окуня (Lepomis gibbosus), чебачка амурського (Pseudorasbora parva) та бичка-кругляка (Neogobius melanostomus) в різних умовах існування, оцінили стабільність їх життєвого розвитку. Аналізували кількість променів у міжзябровій перегородці, кількість гіллястих променів у грудних і черевних плавцях, кількість лусок у бічній лінії. Визначали мінливість цих ознак на лівому та правому боці риб. Установлено, що зниження життєздатності природних популяцій риб за впливу негативного антропогенного тиску наразі незначне. Стабільність розвитку риб за аналізом білатеральних ознак відмічається у межах норми – 1 бал (Neogobius melanostomus із водойм природного заповідника «Дніпровсько-Орільський», Lepomis gibbosus і Pseudorasbora parva – із середньої ділянки ріки Самара) або незначно відхиляється від нормативних показників – 2 бали (Lepomis gibbosus із нижньої ділянки Самари). Найнижчі кількісні показники асиметрії білатеральних ознак спостерігаються у Neogobius melanostomu з водойм природного заповідника «Дніпровсько-Орільський» (0,17 асиметричних виявлень на одну ознаку). Це може свідчити про відсутність негативного техногенного впливу на донних риб у межах акваторій, які перебувають під особливою охороною. Застосування аналізу показників флуктуючої асиметрії риб – найбільш простий і доступний спосіб експрес-аналізу стану водного середовища, але для отримання більш точного та достовірного оцінювання необхідно застосовувати складні лабораторні дослідження, у тому числі молекулярні та біохімічні.
Флуктуюча асиметрія риб природних і штучних водойм Придніпров’я на прикладі інвазійних виді
Горчанок Анна Володимирівна https://orcid.org/0000-0003-0103-1477
Keywords: reservoirs of Dnipro Region; водойми Придніпров’я; fluctuating asymmetry; флуктуюча асиметрія; Lepomis gibbosus; сонячний окунь; Pseudorasbora parva; чебачок амурський; Neogobius melanostomus; бичок-кругляк